Factors Associated with Prolonged Parturition - Maida Pardosi (Postgraduate, University of Mataram, 2023)
In Indonesia, the mortality rate for mothers and babies is increasing; one of the causes is prolonged labor. This study aimed to determine the factors associated with prolonged labor events. This type of research is an analytical survey with a cross-sectional research design.Â The study population was all mothers giving birth to as many as 252 people, with a sample of 72 randomly taken. The research instrument uses a checklist sheet. The data used is secondary data obtained from medical records and documentation. Data analysis was carried out using a test thatÂ squares.Â The results showed that based on the age factor with prolonged labor, p-value = 0.018, parity factor with a long struggle, p = 0.001, and the birth weight factor for babies with a long work, p-value = 0.005. Based on this statement, it was obtained that the value of p < Î± where Î± = 0.05 means that there is a significant relationship between age, parity, and birth weight of the baby to long labor. Based on the study's results, it was concluded that the baby's age, equality, and birth weight are related to the incidence of prolonged labor